KAJIAN DETAILED ENGINEERING DESIGN (DED) PABRIK DAN STUDI KELAYAKAN PRODUK MILKY JELLY DENGAN PENDEKATAN KEAMANAN PANGAN DI PERUSAHAAN AINI FOOD INDONESIA - Sunaryo, Endang; Prasetya, Adi; Mardiah (Jurnal Ilmiah Pangan Halal, 2020)
Facing business competition at home and abroad, home industry businesses must be able to prepare themselves and have a strategy to be able to produce quality products. In producing quality food products and safe for consumption, it is necessary to use food safety standards. Aini Food Indonesia is an IRT or IKM that processes food products. The purpose of this study is to analyze and recommend food safety systems such as CPPOB and HACCP, to propose a factory Detailed Engineering Design (DED) and to conduct a financial-based business feasibility study. This research is a descriptive qualitative study, which describes and explains the conditions at IKM Aini Food Indonesia. Based on the results of CPPOB and HACCP analysis, several discrepancies were found and critical points that must be controlled in the process of making milky jelly. The results of this study can be concluded that based on the CPPOB and HACCP analysis, IKM Aini Food Indonesia must make repairs that are incompatible, such as improving infrastructure with the DED design. Based on the business feasibility study analysis, this IKM is feasible to run its business with new investment and add production capacity and sales.